Vpliv jezikovnih dražljajev televizijskih oglasov na čustveno odzivanje z vključitvijo meritve fizioloških parametrov - Premrov, Emira (visokošolska dela, 2016)
The purpose of the Doctoral dissertation is to explore the influence of verbal impulses of selected German and Slovenian television commercials on triggering emotions. The research aims at finding out the interconnection of verbal and psychological dimension of television commercials and the comparison and analysis of the data, obtained with the help of test subjects from two different language and social environments - German and Slovene, including the dimension of the gender of test subjects when measuring their physiological functions. At the same time, it aims at studying and finding out the role of the intensity, quality and type of triggered emotions through the prism of multicultural context. In addition, the standard techniques and instruments of collecting quantity data were applied - a questionnaire, a grading scale and systematic measuring of physiological parameters. The data, obtained with the help of the questionnaires, completed by the test subjects, were statistically analysed with R 2.11.1 and R 3.01 programmes. The results of statistical tests show that the verbal tools, applied in the German and Slovenian commercials concerned, do influence triggering of certain emotions but with the lower percentage of influencing that the non-verbal or combined impulses. The analysis also showed that the influence of verbal impulses of television commercials on triggering emotions depends on the language and cultural environment as well as the gender of participating test subjects, taking into account the exceptions.
Keywords: čustveno odzivanje; disertacije; dissertations; emotional responses; German language; jezikovni dražljaji; nejezikovni dražljaji; nemščina; non-verbal impulses; Slovene language; slovenščina; television commercials; televizijski oglasi; verbal impulses